A Multinational Cost-Consequence Analysis of a Bone Conduction Hearing Implant System—A Randomized Trial of a Conventional vs. a Less Invasive Treatment With New Abutment Technology - van Hoof, Marc; Wigren, Stina; Ivarsson Blechert, Johan; Molin, Mattias; Andersson, Henrik; Mateijsen, D. J. M.; Bom, Steven J. H.; Calmels, M. N.; van der Rijt, Antoon J. M.; Flynn, Mark C.; Tongeren, Joost van; Hof, Janny R.; et al. (Frontiers in Neurology, 2020)
Background It is hypothesized that a surgical procedure for placement of the implant/abutment combination leaving the subcutaneous tissues intact will improve cosmetic and clinical results, increase quality of life (QoL) for the patient, and reduce medical costs. Here, incremental costs and consequences associated with soft tissue preservation surgery with a hydroxyapatite(HA)-coated abutment (test) were compared with the conventional approach, soft tissue reduction surgery with an all-titanium abutment (control). Methods A cost-consequence analysis was performed based on data gathered over a period of three years in an open randomized (1:1) controlled trial (RCT) running in four European countries (The Netherlands, Spain, France and Sweden). Subjects with conductive or mixed hearing loss or single-sided sensorineural deafness were included. Results During the first year, in the Netherlands (NL), France (FR) and Spain (ES) a net cost saving was achieved in favor of the test intervention because of a lower cost associated with surgery time and adverse event treatments (NL €86 (CI -50.33; 219.20), FR €134 (CI -3.63; 261.30), ES €178 (CI 34.12; 97.48)). In Sweden (SE), the HA-coated abutment was more expensive than the conventional abutment, which neutralized the cost savings and led to a negative cost (SE €-29 CI -160.27; 97.48) of the new treatment modality. After three years, the mean cost saving reduced to €17 (CI -191.80; 213.30) in the Netherlands, in Spain to €84.50 (CI -117.90; 289.50) and in France to €80 (CI -99.40; 248.50). The mean additional cost in Sweden increased to €-116 (CI -326.90; 68.10). The consequences in terms of the subjective audiological benefit and HRQoL were comparable between treatments. A trend existed for favorable results in the test group for some consequences and statistical significance is achieved for the cosmetic outcome as assessed by the clinician. Conclusions From this multinational cost-consequence analysis it can be discerned that health care systems can achieve a cost saving during the first year that regresses after three years, by implementing soft tissue preservation surgery with a HA-coated abutment in comparison to the conventional treatment. The cosmetic results are better.